Pemberdayaan Mahasiswa D-IV Manajemen Pemerintahan Universitas Jambi dalam Kampanye Zero Waste di Kampus - Ovie Yanti; Erwita Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
Diploma IV Government Management is one of the study programmes in the Faculty of Economics and Business, Jambi University. As one of the study programmes that supports the Green Faculty Concept, D-IV Government Management participates in keeping the campus environment clean through the Zero Waste campaign. Given the green campus environment full of various kinds of plants, of course, it produces a lot of leaf waste. Coupled with the habit of students who like to gather and discuss under the trees by bringing food or drinks in packaging, contributes to the amount of waste in the campus environment. Through student empowerment activities, it is hoped that it can increase the awareness of all campus residents to keep the environment clean so that it is free from waste.